Experiences regarding internship among Bachelor of Science in nursing students in Peshawar: A qualitative study - Israr Ahmad; Sardar Ali; Asmat Shaheen (Journal of the Pakistan Medical Association, 2022)
Objectives: To explore the experiences of new nursing graduates during their internship in a tertiary care setting. Method: The qualitative phenomenological descriptive study was conducted from September2020to May2021 at three private hospitals of Peshawar, Pakistan, namely the Kuwait Teaching Hospital, the Mercy Teaching Hospital and the Prime Teaching Hospital. New nursing graduates of either gender were enrolled. Data was collected through semi-structured interviews using an interview guide and probing questions. Data was analysed using the 6-step Braun and Clarke method. Results: Of the11 subjects, 6(54.5%) were males and 5(45.5%) were females. Data led to the generation of four main themes; challenges, coping strategies, improved knowledge, and need for improvement in internship programme. The participants said certain types of individuals and organisational challenges affected them both personally and socially in their daily routines. Coping strategies varied among the subjects. Conclusion: New nursing graduates faced both individual and organisational challenges which is a matter of concern. Policies and their proper implementation should be planned to counter such challenges. Key Words: New nursing graduates, Internship programme, Challenges, Experiences, Clinical practice.